Social protection and asset accumulation - Hidrobo, Melissa; Hoddinott, John F.; Kumar, Neha; Olivier, Meghan (International Food Policy Research Institute, 2014)
Social protection emerged as a policy tool to address poverty and vulnerability in developing countries. In recent years, international donor organizations as well as national governments of many developing countries have adopted social protection strategies. As a result there has been a rapid increase in the number of social protection programs and the total number of beneficiaries these cover. There are a plethora of definitions of social protection ranging from the narrow to the expansive.